Insights into the molecular and genetic role of obesity in breast cancer pathogenesis - Sandeep Mallya; Varsha Gangadhar; Sophia Evangeline Aldrin; Meghana Acharya; Shama Prasada Kabekkodu; Kiran Kumar Kolathur; Sanjiban Chakrabarty (Cancer Biology & Therapy)
The epidemic of obesity is a growing concern and is one of the major risk factors for several chronic diseases, including several types of cancers. The correlation of breast cancer with obesity has been extensively studied and involves an interplay of hormonal, metabolic, and genetic factors explored in this review. Inflammation and hormone dysregulation play an important role in promoting a protumorigenic environment through adipose tissue, which is involved in energy storage and functions as an endocrine organ. As a result, various cytokines, primarily proinflammatory in nature, are released, resulting in low-grade inflammation promoting tumor growth. Additionally, obese conditions also induce imbalances in hormones, particularly estrogen and insulin, both of which drive carcinogenesis. Genetic components such as single nucleotide polymorphisms also play critical roles in modulating the correlation between obesity and breast cancer. This review provides a comprehensive overview of various mechanisms underlying obesity and breast cancer incidence and progression.